Pemanfaatan Nilai Budaya Ra’ian dalam Strategi Pendidikan Agama Kristen bagi Pembentukan Karakter Pemuda di Desa Sawang Utara Kecamatan Melonguane - Darinding, Jane Lestari; Heydemans, Ester; Lalompoh, Cyrus; Tulung, Jeane Marie (Tumou Tou, 2021)
The purpose of this research is to describe and analyze the characteristics and realities of the Ra'ian culture, the christian education strategy for the Ra'ian culture, the supporting and inhibiting factors and the efforts to implement the Rai'an cultural values ​in building the youth character. This research method is the descriptive qualitative research conducted in the North Sawang Village, Melonguane District in 2020. The data were collected through observation, interviews and documentary study. From the outcomes of the data analysis and interpretation, it is found that; (1). In reality, this Rai’an culture contains positive meaning in accordance with Christian teachings and has cultural values ​​that can be used as substance for the character building. The Rai’an culture has undergone a shift due to a lack of knowledge from the youth about the Rai’an culture. (2). Advice and sermons as the ways to build the character as they contain teachings based on the gospel, as well as the applicaton or approach of the five movements of the Groome as a way of instilling rai’an cultural values, 3). The supporting factors, namely parents at home who also collaborate with traditional elders, village leaders and religious figures, make customary activity programs. The inhibiting factors of social and Technology Advancements are uncontrollable use of collphones (online games) but also the social environment that drivers them to carry out deviant behavior. (4). The effort that can be made is to involve the youth in organizational activities in the village and in the church as well as seminars containing the cultural wealth that exists in the Talaud Island Regency, especially those in the village of North Sawang. As a conclusion of these findings, this Rai’an culture must be introduced to the youth properly in the way of utilizing the cultural values ​​as the teaching materials by Christian educators. The parents and the leaders of the village, custom and church work together to formulate programs in building the youth character.